Challenges in the Implementation of Groundwater Tax Collection in Sumedang Regency: A Fiscal Decentralization Perspective and Islamic Normative Support - Hertin Nur Cahya (International Journal of Nusantara Islam, 2026)
This study examines the implementation challenges of the Groundwater Tax (Pajak Air Tanah, PAT) in Sumedang Regency from the perspective of fiscal decentralization and Islamic normative support for Sustainable Resource governance. Drawing on audited financial reports for the 2022-2024 fiscal years and a review of taxation, water resource, and licensing regulations, the study finds that PAT realization consistently fell short of the target, dropping from 64.15% in 2023 to 55.57% in 2024, despite high extraction potential. These weaknesses are driven by partial revenue assignment, reliance on provincial authorities to determine the Groundwater Acquisition Value, regulatory disharmony, licensing delays, and weak inter-agency coordination. Beyond institutional constraints, Islamic ethical principles – khalifah (stewardship), israf (prohibition of waste), and maslahah (public interest) – reinforce the legitimacy of groundwater taxation for environmental protection and social welfare. The study highlights the urgency of harmonizing regulations, strengthening administrative capacity, and integrating licensing and taxation systems.